Evaluating the feasibility and effectiveness of a capacity-building model to nurture junior independent clinical research investigators in Uganda - Aidah Nanvuma; Joseph Musaazi; Adelline Twimukye; Vivian Nakate; Agnes Kiragga; Miriam Laker-Oketta; Christine Sekaggya-Wiltshire; Yukari C. Manabe; Barbara Castelnuovo (PLoS ONE, 2026)
Background Research capacity-building initiatives remain crucial to achieving Sustainable Development Goal 3 on health and well-being, especially in LMICs. We aimed to evaluate the effectiveness of the Infectious Disease Institute’s (IDI) Capacity-Building Model to nurture junior independent clinical research investigators in Uganda. Methods From 13 th July 2021–06 th February 2023, we conducted a cross-sectional study using a mixed-methods approach to assess the extent to which the Capacity-Building Model was effective, feasible, and acceptable. For quantitative research, we conducted an online survey with 80 scholars (Master’s, PhD, and Post-doctoral fellows), comprising 20 alumni and 60 current scholars, to explore their experiences and perceptions as former and current scholars of the Capacity Building Unit (CBU) at IDI. For qualitative research, we purposively selected 20 scholars to participate in the in-depth interviews. Results Participants reported that the capacity-building Model had a beneficial impact on their career progression, with 90% expressing a willingness to recommend it to others. The overall scientific benefit reported was 48.7%; this was significantly higher among continuing scholars than among alumni (56.7% vs 25.0%, respectively; p-value = 0.046). Additionally, 85% achieved their career goals, and 65% said it expanded their employment opportunities. Qualitative findings highlighted its significant positive impact on research training and professional development. Participants praised the Model’s emphasis on mentorship, with both scientific and non-scientific support proving crucial in guiding junior researchers through technical challenges, manuscript writing, and career planning. Soft skills training, dissemination platforms, and networking opportunities further contributed to scholars’ academic growth. Scholars benefited from robust institutional support, including access to research infrastructure, grantsmanship assistance, and administrative systems. However, challenges such as limited research funding, slow procurement processes, and delays in supervision hindered progress. The COVID-19 pandemic also disrupted mentorship and training. Participants recommended improvements in mentorship coordination, procurement efficiency, broader model visibility, and expansion to other universities and disciplines to enhance its effectiveness and sustainability. Conclusion Overall, the Capacity-Building Model was highly acceptable among scholars; however, minor administrative challenges need to be addressed to further enhance learning. We recommend tailored, relevant scholarly programs to meet the evolving needs of emerging scientists and foster scholarly growth and research innovation in academic institutions, enabling them to tackle local public health challenges. Future research is required to assess the cost of capacity building and its sustainability.